POTENTIAL MAPPING IN AN EFFORT TO REALIZE SUSTAINABLE ECOTOURISM DESTINATIONS. CASE STUDY: ARANYA FOREST - SriHadi, Cecilia V; Rahayu, Siti (RADJA PUBLIKA, 2025)
The importance of considering the potential of a location that will be used as an ecotourism destination is carried out in an effort to ensure the sustainability of the ecotourism destination in the future. This study aims to examine the potential for developing a forest- and community-based ecotourism destination in Aranya Forest in Bogor Regency, with a focus on social and environmental sustainability. The research method is descriptive qualitative with data collection through observation, interviews and triangulation. Data analysis was conducted using NVIVO 12 Pro software. The results of the study indicate that Aranya Forest has great potential to be developed as a sustainable ecotourism destination. The potential wealth of natural resources, the enthusiasm of the management, and the active participation of stakeholders including the local community. There are several obstacles such as limited infrastructure, ineffective promotion, and a lack of human resources. This study concludes that Aranya Forest is capable of becoming a leading destination that offers a pleasant tourism experience, while contributing to local economic empowerment and sustainable environmental conservation.